Книга Еноха - Ганич, О. К. (ХНУРЕ, 2023)
The thesis is devoted to one of the most important apocryphal texts that contain many details about divine visions, prophecies, and ancient myths about the creation of the world and the end of the world. In its content, The Book of Enoch is important for many religious traditions, including Judaism, Christianity, and Islam. However, it also has great interest for philosophers and religious researchers who study it firom philosophical, sociological, and historical perspectives.